Diversity and distribution of stored grain insects among the Soliga Tribal settlements of Biligirirangana Hills, Karnataka, India. (May 2015) - Naveena, Nadur L.; Subramanya, Suryanarayana; Setty, Siddappa
Abstract: Soligas are a tribal community living in the forest areas of Biligirirangana Hills in southern Karnataka, India. Soligas cultivate several crops in small patches located close to their settlements for subsistence. During the present investigation, the diversity, distribution and abundance of insects that infest food grains stored by Soligas were studied and the influence of biotic and abiotic factors was assessed. Grains held in storage by Soligas were found to be infested by 13 species of insects. The distribution and abundance of all the species were mapped. Among these, Sitophilus oryzae was the most widely occurring and abundant species, while, Corcyra cephalonica was the least abundant and less frequently occurring species. Species richness was influenced by the number of food grain types stored by Soligas . It was observed that the biotic and abiotic factors did not influence the diversity and distribution of stored grain insects. Instead, the observed pattern of stored grain insect distribution was found to be influenced by anthropogenic factors like food grain sharing habits among the Soligas and accessibility to the towns and cities from their settlements. Highlights: Thirteen different Stored Grain Insects (SGI) were recorded in the Soliga tribal settlements in Biligirirangana Hills (BR Hills). Diversity and distribution of these insects were mapped. Anthropogenic factors like, grain sharing pattern among Soligas and closeness of Podus to cities and towns were found to be the main factors responsible for the occurrence of and the observed distribution pattern of SGI in BR Hills.